Enhancing Distance Learning: A Framework for E-Learning Strategy and Assessment at Universitas Terbuka Indonesia - Dwi Putranto Riau; Erlambang Budi Darmanto; Bachtiar Bachtiar (Edumaspul: Jurnal Pendidikan, 2023)
Due to the diverse educational backgrounds and digital skills of students in both undergraduate and graduate programs at Universitas Terbuka, there is a need to optimize the institution's e-learning program. This study aims to find out the concept of the implementation of e-learning strategies for the students of Universitas Terbuka and the evaluation process of the e-learning conducted in the distance learning mode. This research used descriptive qualitative research, employing two research instruments: semi-structured interviews and document analysis. Ten graduate students who have two years’ experience with the Universitas Terbuka e-learning activities were invited in the semi-structure interviews. Data analysis follows the interactive analysis model and SWOT Analysis. These stages collectively yield strategies for implementing e-learning learning and the evaluation of e-learning learning. The results of this study show that the e-learning implemented in Universitas Terbuka has greatly helped the students to follow the UT learning process effectively and has greatly improved the overall e-learning experience for the students. The findings from this research also show that diverse learning resources are able to cater the various learning styles and preferences, as well as enhancing student engagement and understanding. Some recommendations in relation to the implementation of e-learning are provided.